Pengaruh Kompetensi, Employee Relations dan Organizational Citizenship Behavior (OCB) terhadap Kinerja Karyawan BTN Syariah Cabang Tangerang - Idelia, Aramita Dinah; Hadiwijaya, Dudung; Muttaqijn, Muhammad Imam (Universitas Batanghari Jambi, 2024)
This research aims to test and determine the influence of competence, employee relations, and organizational citizenship behavior (OCB) on the performance of BTN Syariah Tangerang Branch employees. The method used is quantitative research using saturated sampling techniques, namely the entire population, namely 40 respondents, is used as the research sample. Data collection was carried out using questionnaires and observations. This research uses data analysis techniques, namely multiple linear regression analysis. The research results found that competence, employee relations and organizational citizenship behavior had a positive and significant influence on the performance of BTN Syariah Tangerang Branch employees.